Transilluminating testicular mass - Santosh Kumar Mahalik; Alpana Prasad; Suneeta Bhalla; Rajeev Kulshrestha (Indian Journal of Medical and Paediatric Oncology)
Testicular tumor in prepubertal age group is uncommon. Most of the testicular tumors are benign in this age group and present as painless, hard testicular mass. We present a case where a 7 year male child presented to us with painless scrotal swelling, which was cystic and transilluminating, clinically mimicking as hydrocele. On ultrasonography, the mass was solid. Orchidectomy was performed and histopathology revealed mature cystic teratoma.